The Development of an Android-Based Interactive Learning Media to Enhance Understanding of OP-AMP Application as a Temperature Sensor Controller - Irawan, Dodi; Khumaedi, Muhammad; Kusumawardani, Rini (Universitas Negeri Semarang, 2023)
The utilization of OP-AMP as controllers for temperature sensors plays a crucial role in both the manufacturing and automation sectors. Nevertheless, traditional learning approaches often fail to engage students, leading to diminished interest and lower academic performance. To address this issue, an interactive learning media based on Android technology is being developed, aimed at enhancing current teaching methods and improving students' understanding of OP-AMP applications in temperature sensor control. The objectives of this study are threefold: (1) to analyze the viability of the developed learning media, (2) to evaluate the impact on learning outcomes, and (3) to compare the learning improvements between this new media and traditional teaching methods. The research follows the ADDIE model, with data collection carried out via pre-tests and post-tests. Media feasibility was evaluated using CVR and CVI tests, while the cognitive test's validity was measured through Aiken's V and ICC. Data analysis employed a two-tailed t-test and N-Gain calculation. The study involved 72 eleventh-grade students from the Industrial Electronics Engineering program at SMK NU Ungaran. Results indicated that the Android-based interactive learning tool was highly effective, with a CVR above 0.75, an Aiken's V score of 0.90, and an ICC value of 0.797. Moreover, this learning media significantly enhanced students' academic performance, with a t-value of 30.234 and a p-value of 0.000. The experimental group saw a 74.4% improvement in learning outcomes, compared to 67.4% in the control group, demonstrating the media’s effectiveness in teaching OP-AMP applications.